PECULIARITIES OF DIVERSIFICATION OF HIGH EDUCATIONAL ESTABLISHMENTS IN THE INFORMATION AGE - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the analysis of Ukrainian and foreign philosophers’ approaches to the problem of diversification of high educational establishments is given. Specificity of a variety of these educational institutions in the period of establishing of the information society is represented.